2021
DOI: 10.52711/0974-360x.2021.00543
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Sub-acute Toxicity study of Amrtadi Churna

Abstract: Amrtadi Churna is an Ayurvedic polyherbal formulation containing three herbs viz., Amalaki (Emblica officinalis), Gokshur (Tribulus terrestris) and Guduchi (Tinospora cordifolia). It is prescribed in India for immunomodulation and treating hyperacidity. The present work reports the acute and sub-acute toxicity assessment of Amrtadi Churna on experimental animals to rule whether it might produce toxicity on herb-herb interactions by combining its ingredient. The results showed that, the single administration of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…The acute and subacute toxicity of Amrutadi churna , an Ayurvedic poly herbal formulation made of three herbs ( Tribulus terrestris , Emblica officinalis , Tinospora cordifolia ), was evaluated in rats. Toxicologically, when rats were even fed with higher dose of Churna (5000 mg/kg) it caused neither death nor severe toxicity in rats [ 59 ], which outlines the non-toxic nature of traditional herbs. Cisplatin toxicity was prevented in mice when T. terrestris fruit extract was administered orally at levels of up to 500 mg/kg body weight [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The acute and subacute toxicity of Amrutadi churna , an Ayurvedic poly herbal formulation made of three herbs ( Tribulus terrestris , Emblica officinalis , Tinospora cordifolia ), was evaluated in rats. Toxicologically, when rats were even fed with higher dose of Churna (5000 mg/kg) it caused neither death nor severe toxicity in rats [ 59 ], which outlines the non-toxic nature of traditional herbs. Cisplatin toxicity was prevented in mice when T. terrestris fruit extract was administered orally at levels of up to 500 mg/kg body weight [ 60 ].…”
Section: Discussionmentioning
confidence: 99%
“…Lately, T. terrestris hydroethanolic fruit extract, when dispensed at the rate of 100 mg/kg b.w., for 30 days, altered the negative effects on hematological parameters in male Wistar rats induced by acephate. Recently, hematology, serum biochemistry, and organ histology studies demonstrated that Amrutadi churna containing Emblica officinalis , T. terrestris , and Tinospora cordifolia did not cause hazardous effects at tested dose levels of 500 and 1000 mg/kg b.w, but it caused a mild hyperbilirubinemia with no liver damage [ 59 ].…”
Section: Discussionmentioning
confidence: 99%